PENGARUH KONSENTRASI EKSTRAK BAWANG MERAHDAN MEDIA TANAM TERHADAP PERTUMBUHANSTEK MUCUNA (Mucuna bracteata) - Yuliatul Muslimah; Muhammad Jalil; Wira Hadianto Hadianto; Teuku Sarwanidas; Abu Hasan (Universitas Teuku Umar, 2018)
This research aims to determine the effect of onion extract and media towards growth mucuna cuttings, as well as whether there is interaction between the two factors. This research was conducted in Krueng itam village Tadu Raya Sub-District, Nagan Raya regency from 1 July to 4 September 2012. This research used randomized block design (RBD) factorial design with three replications. The factor of this researchare concentration of extract onion and plant medium. Onion extract consists of 5 levels concentration 0 ml, 5 ml, 10 ml, 15 ml and 20 ml per liter of water. Plant medium (soil: manure) consists of three levels 2: 1, 3: 1 and 4: 1. The results showed that concentrations of the extracts of onion geve significant effect against the number of roots of mucuna age 60 HST,significant effect against shoot on 40 and 60 after day plant andnot significant against the number of shoots. The best of growth cuttingfound at 15 ml concentration of onion extract per liter of water. The plant medium effected was not significant on high shoots towards 40 and 60 after day plant, amount of mucuna shoots and number of roots on 60 after day plant. Therewas asignificant interaction between extract of onions and plant media againstthe root length of mucuna. The best length of root found at concentrations of 10 ml of onion extract per liter water,plant media with 2:1(soil: manure). Keywords : Onion extract, vegetative, medium, mucuna